2019
DOI: 10.31832/smj.490740
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık Bilimleri Öğrencilerinde Temporomandibular Eklem Disfonksiyon Riskinin Araştırılması

Abstract: Amaç Bu çalışmanın amacı, üniversite öğrencilerinde Temporomandibular eklem (TME) disfonksiyon gelişme riskini değerlendirmek; disfonksiyonu tetikleyen faktörler ile yaşam kalitesi, boyun disabilitesi ve psikolojik durum arasındaki ilişkiyi incelemektir. ( Sakarya Tıp Dergisi 2019, 9(2):258-265 ) Gereç ve Yöntemler Dâhil edilme ve dışlanma kriterlerine göre sağlık bilimleri fakültesindeki 197 gönüllü öğrenci değerlendirildi. Değerlendirmede disfonksiyon gelişme riski TME ile ilişkili tetikleyici faktörlerin va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Studies have reported that TMD is more common in women than men (Özdinç et al, 2020;Kaynak et al, 2019;Gas et al, 2021). This is in line with the study that found women are more prone to TMD than men (1.6 to 1) (Basafa and Shahabee, 2016).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Studies have reported that TMD is more common in women than men (Özdinç et al, 2020;Kaynak et al, 2019;Gas et al, 2021). This is in line with the study that found women are more prone to TMD than men (1.6 to 1) (Basafa and Shahabee, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…There are many studies evaluating the frequency of TMD in university students using FAI. In these studies, the prevalence of TMD was found to be 60%, 60%, and 55%, respectively (Özdinç et al, 2020;Kaynak et al, 2019;Bicaj et al, 2017).…”
Section: Discussionmentioning
confidence: 95%